PENGARUH MODEL BRAIN BASED LEARNING TERHADAP HASIL BELAJAR SISWA - Achmad Syarifudin; Risdiana Chandra Dhewy; Eka Nurmala Sari Agustina (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2021)
To see the improvement of students in the learning process, one of which is the value of learning outcomes. To make students an active role in the learning process of rectangular trapezoidal material in class, a Brain Based Learning model can be applied in which students are asked to actively explore knowledge to improve learning outcomes. This study aims to determine the influence of the Brain Based Learning model on student learning outcomes in rectangular material. This research is an experiment using a quantitative approach, which was carried out in the 2020/2021 school year at SMP Kemala Bhayangkari 7 Porong with a sample of 29 students in class VII-A. The results of this study indicate that student learning outcomes on the material of the rectangular trapezoidal shape seen from the value of t = 2.797> t table = 2.051 with a significant probability condition (0.009) less than α (0.05). Also, it is shown by the linear regression equation, namely -253,494 + 3,808X which shows that if the Brain Based Learning model is implemented better with careful preparation so that student learning outcomes improve well. The Brain Based Learning model has a contribution/influence of 22.5% on the learning process of the rectangular material.